2020
DOI: 10.3390/cancers12082146
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Grip Strength in Patients with Unresectable Hepatocellular Carcinoma Treated with Lenvatinib

Abstract: Although sarcopenia is characterized by a loss of muscle strength and skeletal muscle mass, few studies have evaluated the effect of muscle strength on hepatocellular carcinoma (HCC) patients. We evaluated the impact of sarcopenia-related factors (grip strength (GS) and the skeletal muscle index (SMI)) on the survival among lenvatinib-treated unresectable HCC (u-HCC) patients. This single-center cohort study was conducted at a university hospital. The study population included 63 lenvatinib-treated u-HCC patie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 38 publications
(52 reference statements)
2
36
0
Order By: Relevance
“…18 records didn't meet the inclusion criteria and were discarded: 2 involving other kinase inhibitors (Nault et al, 2013[ 28 ], 2015[ 29 ]), 9 with overlapped patient data (Antonelli et al, 2018[ 2 ]; Gigante et al, 2015[ 13 ]; Hoshino et al, 2015[ 16 ]; Imai et al, 2015[ 17 ], 2019[ 19 ]; Labeur et al, 2018[ 23 ][ 24 ]; Okada et al, 2019[ 33 ]; Saeki et al, 2019[ 34 ]), 5 lacking HR and 95 % CI (Mir et al, 2012[ 26 ]; Okada et al, 2020[ 32 ]; Saeki et al, 2018[ 35 ]; Uchikawa et al, 2020[ 39 ]; Ueki et al, 2016[ 40 ]), 1 without any interesting outcome (Cheng et al, 2019[ 7 ]) and 1 with low quality and faulty data (Nishikawa et al, 2017[ 30 ]). Thus, 11 retrospective studies (Antonelli et al, 2018[ 3 ]; Endo et al, 2020[ 10 ]; Hiraoka et al, 2017[ 15 ]; Imai et al, 2020[ 18 ]; Labeur et al, 2019[ 25 ]; Naganuma et al, 2017[ 27 ]; Sawada et al, 2019[ 36 ]; Takada et al, 2018[ 38 ]; Uojima et al, 2020[ 41 ]; Wu et al, 2021[ 43 ]; Yamashima et al, 2017[ 45 ]) were included in this meta-analysis, comprising 1148 patients. The flow diagram of this study selection process is shown in Figure 1 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…18 records didn't meet the inclusion criteria and were discarded: 2 involving other kinase inhibitors (Nault et al, 2013[ 28 ], 2015[ 29 ]), 9 with overlapped patient data (Antonelli et al, 2018[ 2 ]; Gigante et al, 2015[ 13 ]; Hoshino et al, 2015[ 16 ]; Imai et al, 2015[ 17 ], 2019[ 19 ]; Labeur et al, 2018[ 23 ][ 24 ]; Okada et al, 2019[ 33 ]; Saeki et al, 2019[ 34 ]), 5 lacking HR and 95 % CI (Mir et al, 2012[ 26 ]; Okada et al, 2020[ 32 ]; Saeki et al, 2018[ 35 ]; Uchikawa et al, 2020[ 39 ]; Ueki et al, 2016[ 40 ]), 1 without any interesting outcome (Cheng et al, 2019[ 7 ]) and 1 with low quality and faulty data (Nishikawa et al, 2017[ 30 ]). Thus, 11 retrospective studies (Antonelli et al, 2018[ 3 ]; Endo et al, 2020[ 10 ]; Hiraoka et al, 2017[ 15 ]; Imai et al, 2020[ 18 ]; Labeur et al, 2019[ 25 ]; Naganuma et al, 2017[ 27 ]; Sawada et al, 2019[ 36 ]; Takada et al, 2018[ 38 ]; Uojima et al, 2020[ 41 ]; Wu et al, 2021[ 43 ]; Yamashima et al, 2017[ 45 ]) were included in this meta-analysis, comprising 1148 patients. The flow diagram of this study selection process is shown in Figure 1 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The demographic and characteristics of the 11 eligible studies are shown in Table 1 (Tab. 1) (References in Table 1: Antonelli et al, 2018[ 3 ]; Endo et al, 2020[ 10 ]; Hiraoka et al, 2017[ 15 ]; Imai et al, 2020[ 18 ]; Labeur et al, 2019[ 25 ]; Naganuma et al, 2017[ 27 ]; Sawada et al, 2019[ 36 ]; Takada et al, 2018[ 38 ]; Uojima et al, 2020[ 41 ]; Wu et al, 2020[ 43 ]; Yamashima et al, 2017[ 45 ]). Out of these retrospective studies, 9 were performed in Asia (8 in Japan and 1 in China) and the remaining 2 in Europe (Netherlands and Italy).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, those studies had individually defined cut‐off values for a low SMI and were not guideline‐based. More recent studies have reported that low grip strength (muscle strength) has a greater effect on the prognosis than a low skeletal muscle mass in patients with CLD as well as patients with HCC treated with lenvatinib 45–47 . In fact, the European Working Group on Sarcopenia in Older People (EWGSOP) guidelines state that a low muscle strength is the primary parameter of sarcopenia, as muscle strength is the most reliable measure of the muscle function 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Another retrospective study showed that the OS of patients with a normal grip strength (GS) was better than that in those with decreased GS, and a normal GS was found to be significantly associated with OS in a multivariate analysis [104]. While the ORR and PFS did not differ to a statistically significant extent between the two groups, the post-progression survival in patients with a normal GS was longer in comparison to that in patients with decreased GS, which indicated that patients with a normal GS may be more likely to have a maintained liver function and PS, raising the possibility of anticancer therapy after progression [104]. Although studies concerning sarcopenia have been limited, Sarcopenia might impact the therapeutic efficacy of lenvatinib treatment.…”
Section: The Relationship Between Sarcopenia and Overall Survivalmentioning
confidence: 99%